Application of ISAK 35 for non-profit organizations a study on foundations in Indonesia - B. Sundari; Ary Natalina; Agustina Nicke Kakiay (Jurnal Mantik, 2023)
Financial reporting standards for non-profit organizations are not explicitly regulated in Financial Accounting Standards (SAK), but the Accounting Standards Board (DSAK) issued Interpretation of Financial Accounting Standards (ISAK) 35. ISAK 35 contains guidance for the Presentation of Financial Statements of Non-profit Oriented Entities. The foundation is a part of a non-profit organization. This study aims to determine the arrangement, form and content of financial statements in one of the foundations of non-profit organizations in Jakarta based on ISAK 35. This research method uses a qualitative approach and descriptive method to analyze the application of ISAK 35 to one of the foundations in Jakarta, related to the presentation of financial statements non-profit-oriented entity for the 5 years in the period 20X1-20X5. The results of this study indicate that the foundation's financial reports are not in accordance with applicable standards and there is weak internal control over financial transactions